Role of doping-induced photochemical and microstructural properties in the photocatalytic activity of InVO4 for splitting of water - Rakesh, K.; Khaire, S.; Bhange, Deu S.; Dhanasekaran, P.; Deshpande, Suvarna S.; Awate, S. V.; Gupta, N. M. (Journal of Materials Science, 2011)
We report in this paper on microstructural, optical and photocatalytic properties of single-phase indium orthovanadates, as a function of doping at lattice sites. The UV-visible spectra of these samples exhibited intense UV-region bands at 250 and 350 nm, besides broad absorption band in visible region (350-700 nm). The wavelength at absorption edge and the intensity of visible absorption showed considerable increase on doping of an impurity, particularly at V or O lattice sites. Also, the samples gave rise to blue-green photoluminescence emission, with overriding bands at ca. 420, 450, 460 and 485 nm, on excitation at 240-420 nm wavelengths. The intensity of these fluorescence bands varied with excitation wavelength and impurity content of a sample. In deviation with several earlier studies, only oxygen and no hydrogen were produced during photocatalytic splitting of water, in the experiments conducted under visible light (> 395 nm) and at a pH of similar to 6.5. The O-2 yield depended on the dispersed metal co-catalyst, impurity content and the addition of methanol as sacrificial reagent. On the other hand, small quantities of hydrogen and no oxygen were evolved on UV-irradiation of pure water using metal/InVO4. These results are ascribed to flat band potentials and the doping-induced inter-band donor and acceptor charge trapping states of InVO4, the presence of which is revealed by XRD, luminescence and XPS studies. Our study also confirms that the onset of absorption edge may not necessarily correspond to band-to-band energy gap of a semiconducting material. This accounts for some anomalous band gap energies reported earlier for InVO4.